Indirect measurement of flow of liquid pumped with pump packages; Petroleum and Coal; Vol. 59, iss. 2 - Maystrenko A. V. Andrey Vasiljevich; Svetlakov A. A. Anatoly Antonovich; Gandzha T. V. Taras Viktorovich; Aksenova N. V. Nataliya Valerievna (2018, 2018)
Title screen